An analysis of the elementary art education curriculum in Iran / Minoo Aiatollahi Tabar - Minoo Aiatollahi, Tabar (2015)

(untitled)
The aim of this research was to look at the practice of art education in Iranian elementary schools. This was done by examining the structure of art curriculum and the way it was translated into teaching practice in the schools. This attempt was also to chart out the status of the art curriculum, and to suggest possible alternatives for its improvement. This study involved three forms of examination in the process of evaluation, each of which engaged a different method of data collection. To identify the objectives, approaches, and content of the curriculum, the method of examination involved collecting information from documents, using the content analysis approach. To examine the way art was taught in the classroom, the method involved a survey with sets of prepared questionnaires, plus observation. The third method used to determine the effects of teachers’ performance on students’ learning of art was a class test for assessing knowledge, skill, and attitude of children in the selected grade. Purposeful sampling was done on a total of 18 schools from three states in Iran. From these 18 schools, 81 teachers were selected to participate in the survey and 440 students in knowledge and attitude tests. The art curriculum in Iran focused heavily on “making” activities in two main areas, namely painting and handicrafts. Given this focus, children were to assume art learning mostly by producing works with less concern on art appreciation. There were no expressed philosophical and instructional contents appearing in major statements of the curriculum. This makes the meaning of visual art as a learning subject in schools less congruent with the global objective; thus, jeopardizing the target of developing visual literacy among Iranian children. Besides that, the current practice of art training for these non-specialist teachers in elementary school was only through in-service program with less than forty hours of instruction. Because of this limited exposure, ii teachers were inadequately equipped, thus lacking well-grounded knowledge and skills in art teaching. The obvious neglect in the components of aesthetics and critical thinking as shown in the contents of teachers’ handbooks, has contributed to the imbalance in the gist of art contents, only to end up with sidelining the notion of studying cultural heritage through visual art. Having poor support in educational facilities for art, teachers were faced with another critical issue in classroom teaching. Their access to sufficient materials and equipment in art teaching, what more new technology in art education left much to be desired. Understandably, the standard of Iranian students’ art knowledge was, therefore, hoping for improvements. Generally, the students have shown limited understanding of art concepts and fundamentals of art knowledge. On the whole, they have not quite succeeded in achieving the desired skills, given that almost three quarters of them did not achieve encouraging results in both painting and handicrafts. Notwithstanding, the students have, in various degrees, shown positive attitude toward art. Their predisposition to art as a result of their learning was measured in terms of their interests, preferences, views of art benefits when asked to self-evaluate their own ability.